Preparation of midwife for independent care for a pregnant woman in the opinion of the inhabitants of the eastern region - Iwanowicz-Palus, Grażyna; Golonka, Ewa; Bień, Agnieszka; Stadnicka, Grażyna (Nursing in the 21st Century, 2013)
PREPARATION OF MIDWIFE FOR INDEPENDENT CARE FOR A PREGNANT WOMAN IN THE OPINION OF THE INHABITANTS OF THE EASTERN REGIONAim. The aim of the study was an attempt to find out the opinion of the Polish society about the preparation of a midwife for independent taking care of a woman in normal pregnancy.Materials and methods. The study was conducted in 2011 by means of the diagnostic survey method applying questionnaire technique. The research tool was a self – constructed questionnaire, which was conducted among 505 respondents who live in the East region of Poland.Results. The study confirmed that a midwife is properly prepared, trained and educated to take care of a woman in normal pregnancy (women – 68.60%, men – 61.79%), which is also regulated by Polish law (women – 15.70%, men – 14.15%). A midwife is a competent person to take care of a woman in normal pregnancy: primi gravida – the first pregnancy (64.95%) as well as the next pregnancy (78.81%). However, is not prepared to take care of a woman in high-risk pregnancy: the first pregnancy (48.72%) and the next pregnancy (50.89%).Conclusions. The midwives are properly prepared, trained and educated to take care of a woman in normal pregnancy. The midwives are competent person to take care of a woman in normal pregnancy but they are not prepared to take care of a woman in high-risk pregnancy. Proper midwife’s professional experience to independently taking care of a pregnant woman should take 5-10 years.